The Lymph Node Microenvironment May Invigorate Cancer Cells With Enhanced Metastatic Capacities - Li, Tianhang; Liu, Tianyao; Zhao, Zihan; Xu, Xinyan; Zhan, Shoubin; Zhou, Shengkai; Jiang, Ning; Zhu, Wenjie; Sun, Rui; Wei, Fayun; Feng, Baofu; Guo, Hongqian; et al. (Frontiers in Oncology, 2022)
Cancer metastasis, a typical malignant biological behavior involving the distant migration of tumor cells from the primary site to other organs, contributed majorly to cancer-related deaths of patients. Although constant efforts have been paid by researchers to elucidate the mechanisms of cancer metastasis, we are still far away from the definite answer. Recently, emerging evidence demonstrated that cancer metastasis is a continuous co-evolutionary process mediated by the interactions between tumor cells and host organ microenvironment, and epigenetic reprogramming of metastatic cancer cells may confer them with stronger metastatic capacities. Lymph node served as the first metastatic niche for many types of cancer, and the appearance of lymph node metastasis predicted poor prognosis. Importantly, multiple immune cells and stromal cells station and linger in the lymph nodes, which constitutes the complexity of lymph node micro-environment. Active crosstalk between cancer cells and immune cells could happen unceasingly within the metastatic environment of lymph node. Of note, diverse immune cells have been found to participate in the formation of malignant properties of tumor, including stemness and immune escape. Based on these available evidence and data, we hypothesize that the metastatic micro-environment of lymph node could drive cancer cells to metastasize to further organs through epigenetic mechanisms.